Case Report: Nasal Cavity Epithelial-Myoepithelial Carcinoma With High Fluoro-D-Glucose Uptake on Positron Emission Tomography/Computed Tomography - Dzuko Kamga, Jacques; Leclere, Jean-Christophe; Uguen, Arnaud; Amrane, Karim; Abgral, Ronan (Frontiers in Medicine, 2021)
Epithelial-myoepithelial carcinoma (EMC) is a rare malignant neoplasm arising most frequently in the salivary glands. EMC accounts for approximately 1 to 2% of salivary gland tumors. Even if nodal and distant metastasis rates is low, tumor staging remains indicated. Here, the authors present the FDG-PET/CT study of a very rare case of biopsy-proven EMC of the left nasal cavity. This PET scan was performed to guide the therapeutic strategy due to an atypical high-grade presentation in immunohistochemistry. To our knowledge, this is the first case reporting such high FDG avidity of EMC of the nasal cavity in PET/CT.